Assessment of the impact strength of the denture base resin polymerized by various processing techniques - Rajashree Jadhav; S V Bhide; P S Prabhudesai (Wolters Kluwer Medknow Publications, 2013)
Aim : To measure the impact strength of denture base resins polymerized using short and long curing cycles by water bath, pressure cooker and microwave techniques. Materials and Methods: For impact strength testing, 60 samples were made. The sample dimensions were 60 mm × 12 mm × 3 mm, as standardized by the American Standards for Testing and Materials (ASTM). A digital caliper was used to locate the midpoint of sample. The impact strength was measured in IZOD type of impact tester using CEAST Impact tester. The pendulum struck the sample and it broke. The energy required to break the sample was measured in Joules. Data were analyzed using Student's " t" test. Results: There was statistically significant difference in the impact strength of denture base resins polymerized by long curing cycle and short curing cycle in each technique, with the long curing processing being the best. Conclusion: The polymerization technique plays an important role in the influence of impact strength in the denture base resin. This research demonstrates that the denture base resin polymerized by microwave processing technique possessed the highest impact strength.